2015
DOI: 10.7314/apjcp.2015.16.11.4583
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a CYP2B6 Gene Polymorphism in Patients with Acute Myeloid Leukemia

Abstract: Background: The objectives of this study aimed to detect a CYP2B6 polymorphism in de novo cases of acute myeloid leukemia patients and identify any role in disease progression and outcome. Materials and Methods: DNA was isolated from peripheral blood of 82 newly diagnosed acute myeloid leukemia cases and the CYP2B6 G15631T gene polymorphism was assayed by PCR restriction fragment length polymorphism (PCR-RFLP). Results: The frequency of the GG genotype (wild type) was 48 (58.5%) and that of the mutant type T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There is strong evidence indicating that CYP2B6 polymorphisms are involved in the development not only of solid tumors, such as breast cancer (Justenhoven et al, 2014) and hepatocellular carcinoma (Yan et al, 2017), but also in hematological malignancies (Alazhary, Shafik, Shafik, & Kamel, 2015;Berkoz & Yalin, 2009;Daraki et al, 2014;Yuan et al, 2011). To date, only three studies have revealed a correlation between CYP2B6 c.516G>T polymorphism and AL (Berkoz & Yalin, 2009;Daraki et al, 2014;Yuan et al, 2011), and one study report that the CYP2B6 c.516G>T polymorphism was not associated with AML prognosis (Alazhary et al, 2015). However, associations between CYP2B6 c.516G>T polymorphism, and the occurrence and prognosis of AL in the Han population of Northwest China have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence indicating that CYP2B6 polymorphisms are involved in the development not only of solid tumors, such as breast cancer (Justenhoven et al, 2014) and hepatocellular carcinoma (Yan et al, 2017), but also in hematological malignancies (Alazhary, Shafik, Shafik, & Kamel, 2015;Berkoz & Yalin, 2009;Daraki et al, 2014;Yuan et al, 2011). To date, only three studies have revealed a correlation between CYP2B6 c.516G>T polymorphism and AL (Berkoz & Yalin, 2009;Daraki et al, 2014;Yuan et al, 2011), and one study report that the CYP2B6 c.516G>T polymorphism was not associated with AML prognosis (Alazhary et al, 2015). However, associations between CYP2B6 c.516G>T polymorphism, and the occurrence and prognosis of AL in the Han population of Northwest China have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has provided insights into the substrates, inducers, inhibitors, and gene polymorphisms of CYP2B6; however, potential correlations between CYP2B6 polymorphisms and tumors, especially the occurrence and prognosis of leukemia, remain to be established. There is strong evidence indicating that CYP2B6 polymorphisms are involved in the development not only of solid tumors, such as breast cancer (Justenhoven et al, 2014) and hepatocellular carcinoma (Yan et al, 2017), but also in hematological malignancies (Alazhary, Shafik, Shafik, & Kamel, 2015;Berkoz & Yalin, 2009;Daraki et al, 2014;Yuan et al, 2011). To date, only three studies have revealed a correlation between CYP2B6 c.516G>T polymorphism and AL (Berkoz & Yalin, 2009;Daraki et al, 2014;Yuan et al, 2011), and one study report that the CYP2B6 c.516G>T polymorphism was not associated with AML prognosis (Alazhary et al, 2015).…”
Section: Discussionmentioning
confidence: 99%